2016
DOI: 10.1186/s13104-016-2085-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated PGP9.5 immunofluorescence staining: a valuable tool in the assessment of small fiber neuropathy?

Abstract: BackgroundIn this study we explored the possibility of automating the PGP9.5 immunofluorescence staining assay for the diagnosis of small fiber neuropathy using skin punch biopsies. The laboratory developed test (LDT) was subjected to a validation strategy as required by good laboratory practice guidelines and compared to the well-established gold standard method approved by the European Federation of Neurological Societies (EFNS). To facilitate automation, the use of thinner sections. (16 µm) was evaluated. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
1
30
0
2
Order By: Relevance
“…amyotrophic lateral sclerosis, [44][45][46] critical illness, 47 and peripheral arterial disease. 48 New techniques to determine the IENFD with indirect immunofluorescence, 49 automated PGP9.5 immunofluorescence staining (laboratory developed test), 50 and 3D analysis 51 have been reported. One study investigated the global spatial sampling in order to determine the epidermal nerve fiber length density (ENFLD) taking into account its biologic complexity.…”
Section: Skin Biopsymentioning
confidence: 99%
“…amyotrophic lateral sclerosis, [44][45][46] critical illness, 47 and peripheral arterial disease. 48 New techniques to determine the IENFD with indirect immunofluorescence, 49 automated PGP9.5 immunofluorescence staining (laboratory developed test), 50 and 3D analysis 51 have been reported. One study investigated the global spatial sampling in order to determine the epidermal nerve fiber length density (ENFLD) taking into account its biologic complexity.…”
Section: Skin Biopsymentioning
confidence: 99%
“…Immunohistochemical staining techniques recommended are bright-field immunohistochemistry and indirect immunofluorescence [28]. PGP9.5 immunofluorescence allows nerves to be visualized using a confocal microscope [29]. Smaller intraepidermal nerve fiber densities (IENFD) in HIV-SN patients correlated with the clinical and electrophysiological severity [30].…”
Section: Clinical Features and Diagnostic Criteriamentioning
confidence: 99%
“…The polyclonal PGP9.5 antibody (Doran et al, 1983) labels a band at 26 -28 kD on Western blot (Krimm et al, 2006, Van Acker et al, 2016, and labels neurons and nerve fibres of peripheral and central nervous system and some neuroendocrine cells (Wilson et al, 1988). The monoclonal SP antibody (Millipore), produced using a hybridoma (Cuello et al, 1979) has shown specificity in radioimmunoassay using recombinant substance P or tissue extracts (Cuello et al, 1979).…”
Section: Antibody Characterisationmentioning
confidence: 99%